Food Sharing With Choice: Influence on Social Evaluation - Wang, Chujun; Huang, Jianping; Liao, Jiangqun; Wan, Xiaoang (Frontiers in Psychology, 2020)
We conducted two studies to investigate the influence of food sharing on people’s social evaluation. In Study 1, the results of an online survey revealed that Chinese adults expected voluntary food sharing to influence the recipient’s social evaluation of the sharer. In Study 2, we ran a laboratory-based experiment in which each participant broke bread with one of two unacquainted individuals. When the participants could choose whom to share food with, they rated the selected person as being more prosocial than the person they did not choose. These results demonstrate the influence of voluntary food sharing with choice on people’s social evaluation of unacquainted individuals, and shed some light on the influence of eating behavior on social perception.